Fungsi Manajamen dalam Al-Quran dan Hadist: Studi Literatur - Basri, Henny Hamdani; Heliwasnimar, Heliwasnimar; Satriadi, Inong (Indo-MathEdu Intellectuals Journal, 2024)
Management is an activity that starts from planning, organizing, mobilizing, supervising to coordinate existing resources to achieve common goals in an organization. In the Islamic view, the function of education management reviewed in the Qur'an has several discussions including: (1) planning, (2) organizing; (3) actuating, and (4) controlling. This paper aims to describe verses, hadiths and the relevance between theories and the interpretation of management functions. This research is library research and is included in the qualitative research approach. Data collection is carried out directly from various relevant literature including the Quran, hadith, books, and research articles. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. The results of data analysis show that the management function has the word of God that regulates it starting from the functions of planning, organizing, moving and supervising